Preparation of fine-grained silica-doped zirconia fibers by electrospinning. Issue 15 (15th October 2017) - Sun, Yajuan; Qu, Jingkui; Guo, Qiang; Song, Jing; Wei, Guangye; Xi, Xinguo; Hou, Guihua; Qi, Tao
Abstract: Zirconia fiber, with its resistance to ultra-high temperature, is irreplaceable in many applications. Herein, a technique combining the sol-gel method and electrospinning was used to fabricate uniform 1D zirconia nanofibers from zirconium polyacetate. A suitable heat treatment process was established, and the effects of spinning parameters and additives on the fiber morphology were investigated using XRD, SEM, TGA, and FTIR. The results showed that addition of silica effectively inhibited grain growth and reduced the grain size to 30–60 nm. By optimizing the electrospinning parameters and the sintering process, fine-grained tetragonal zirconia fibers of 400–700 nm diameter could be produced.